Schistosoma mansoni rSm29 Antigen Induces a Regulatory Phenotype on Dendritic Cells and Lymphocytes From Patients With Cutaneous Leishmaniasis - Lopes, Diego Mota; Oliveira, Sérgio Costa; Page, Brady; Carvalho, Lucas P.; Carvalho, Edgar M.; Cardoso, Luciana Santos (Frontiers in Immunology, 2019)
The immune response induced by Schistosma mansoni antigens is able to prevent immune-mediated diseases. Conversely, the inflammatory response in cutaneous leishmaniasis (CL), although responsible for controlling the infection, is also associated with the pathogenesis of disease. The aim of this study was to evaluate the potential of the S. mansoni Sm29 antigen to change certain aspects of the profiles of monocyte derived dendritic cells (MoDCs) and lymphocytes from subjects with CL in vitro. Expression of surface molecules and intracellular cytokines in the MoDCs and lymphocytes as well as the proliferation of Leishmania braziliensis were evaluated by flow cytometry. Levels of cytokines were evaluated in culture supernatants by ELISA. It was observed that stimulation by rSm29 increased the frequency of expression of CD83, CD80, CD86 and IL-10R in MoDCs compared to non-stimulated cultures. Additionally rSm29 decreased the frequency CD4+ and CD8+ T cells expressing CD28 and increased the frequency of CD4+CD25hi and CD4+CTLA-4+ T lymphocytes. Addition of rSm29 to cultures increased IL-10 levels and decreased levels of IL-12p40 and IFN-γ, while not altering TNF levels compared to non-stimulated cultures. This study showed that rSm29 induced a regulatory profile in MoDCs and lymphocytes and thereby regulated the exaggerated inflammation observed in CL. Considering that there are few therapeutic options for leishmaniasis, the use of rSm29 may be an alternative to current treatment and may be an important strategy to reduce the healing time of lesions in patients with CL.